Kinetics of glycerol biotransformation to dihydroxyacetone by immobilized gluconobacter oxydans and effect of reaction conditions - Raška, Jiří; Skopal, František; Komers, Karel; Machek, Jaroslav (Collection of Czechoslovak Chemical Communications, 2007)
Biotransformation of glycerol to 1,3-dihydroxyacetone was carried out in an isothermal isochoric batch reactor with Gluconobacter oxydans immobilized in poly(vinyl alcohol) gel capsules. The reaction course was described with a three-step kinetic model. Two reaction schemes were proposed and compared with 8 kinetic experiments at 25 °C. The experimental dependences of glycerol and dihydroxyacetone concentrations on reaction time were simulated very well by the autocatalytic model. The effects of reaction temperature and initial concentrations of yeast extract and glycerol were studied. Temperature 25-30 °C, initial yeast extract concentration 2-4 g l-1 and initial glycerol concentration 20-50 g l-1 were found as optimal. The determined rate constants can be used to advantage for industrial production of dihydroxyacetone from glycerol.
Keywords: Acetone; biotransformace; aceton; Gluconobacter oxydans; Biotransformation; biotechnologie; Biotechnology